Picosecond Control of Quantum Dot Laser Emission by Coherent Phonons - Czerniuk, T.; Wigger, D.; Akimov, A. V.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Kuhn, T.; Reiter, D. E.; Bayer, M. (Physical Review Letters)
A picosecond acoustic pulse can be used to control the lasing emission from semiconductor nanostructures by shifting their electronic transitions. When the active medium, here an ensemble of (In,Ga)As quantum dots, is shifted into or out of resonance with the cavity mode, a large enhancement or suppression of the lasing emission can dynamically be achieved. Most interesting, even in the case when gain medium and cavity mode are in resonance, we observe an enhancement of the lasing due to shaking by coherent phonons. In order to understand the interactions of the nonlinearly coupled photon-exciton-phonon subsystems, we develop a semiclassical model and find an excellent agreement between theory and experiment.

Optically Controlled Orbital Angular Momentum Generation in a Polaritonic Quantum Fluid - Luk, S. M. H.; Kwong, N. H.; Lewandowski, P.; Schumacher, Stefan; Binder, R. (Physical Review Letters)

Creation and Manipulation of Stable Dark Solitons and Vortices in Microcavity Polariton Condensates - Ma, Xuekai; Egorov, Oleg A.; Schumacher, Stefan (Physical Review Letters)

Driven Boson Sampling - Barkhofen, Sonja; Bartley, Tim; Sansoni, Linda; Kruse, Regina; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

Multipartite Entanglement of a Two-Separable State - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Quantum Correlations from the Conditional Statistics of Incomplete Data - Sperling, Jan; Bartley, Tim; Donati, G.; Barbieri, M.; Jin, X.-M.; Datta, A.; Vogel, W.; Walmsley, I. A. (Physical Review Letters)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Nanoscale Structure of the Oil-Water Interface - Fukuto, M.; Ocko, B. M.; Bonthuis, D. J.; Netz, R. R.; Steinrück, Hans-Georg; Pontoni, D.; Kuzmenko, I.; Haddad, J.; Deutsch, M. (Physical Review Letters)

Quantum Correlations from the Conditional Statistics of Incomplete Data - Sperling, J.; Bartley, Tim; Donati, G.; Barbieri, M.; Jin, X.-M.; Datta, A.; Vogel, W.; Walmsley, I. A. (Physical Review Letters)

Talbot Effect for Exciton Polaritons - Gao, T.; Estrecho, E.; Li, G.; Egorov, O. A.; Ma, Xuekai; Winkler, K.; Kamp, M.; Schneider, C.; Höfling, S.; Truscott, A. G.; Ostrovskaya, E. A. (Physical Review Letters)
Keywords: General Physics and Astronomy

Single-Mode Parametric-Down-Conversion States with 50 Photons as a Source for Mesoscopic Quantum Optics - Harder, Georg; Bartley, Tim; Lita, Adriana E.; Nam, Sae Woo; Gerrits, Thomas; Silberhorn, Christine (Physical Review Letters)

Engineering the Frequency Spectrum of Bright Squeezed Vacuum via Group Velocity Dispersion in an SU(1,1) Interferometer - Lemieux, Samuel; Manceau, Mathieu; Sharapova, Polina; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Physical Review Letters)
Keywords: General Physics and Astronomy

Local Sampling of the Wigner Function at Telecom Wavelength with Loss-Tolerant Detection of Photon Statistics - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review Letters)
Keywords: General Physics and Astronomy

Nonclassicality Phase-Space Functions: More Insight with Fewer Detectors - Luis, Alfredo; Sperling, Jan; Vogel, Werner (Physical Review Letters)

Full Multipartite Entanglement of Frequency-Comb Gaussian States - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Microwave Experiments Simulating Quantum Search and Directed Transport in Artificial Graphene - Böhm, Julian; Bellec, Matthieu; Mortessagne, Fabrice; Kuhl, Ulrich; Barkhofen, Sonja; Gehler, Stefan; Stöckmann, Hans-Jürgen; Foulger, Iain; Gnutzmann, Sven; Tanner, Gregor (Physical Review Letters)

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.

Uncovering Quantum Correlations with Time-Multiplexed Click Detection - Sperling, Jan; Bohmann, M.; Vogel, W.; Harder, G.; Brecht, Benjamin; Ansari, V.; Silberhorn, Christine (Physical Review Letters)

Structural Quantification of Entanglement - Shahandeh, F.; Sperling, Jan; Vogel, W. (Physical Review Letters)

Pseudorotational Epitaxy of Self-Assembled Octadecyltrichlorosilane Monolayers on Sapphire (0001) - Steinrück, Hans-Georg; Magerl, A.; Deutsch, M.; Ocko, B. M. (Physical Review Letters)